2020
DOI: 10.3390/plants9101386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cadmium-Tolerant Rhizobacteria on Growth Attributes and Chlorophyll Contents of Bitter Gourd under Cadmium Toxicity

Abstract: Cadmium (Cd) is one of the heavy metals that negatively affects the growth of plants. High solubilization in water leads Cd to enter into plants quite easily, thus decreasing seed germination, photosynthesis, and transpiration. It also shows an antagonistic effect with many of the plants’ nutrients like Mn, Ca, K, Mg and Fe. Nowadays, inoculation of plants with ACC deaminase (ACCD) rhizobacteria to mitigate Cd’s adverse effects has drawn the attention of environmental microbiologists. The rhizobacteria secrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 56 publications
6
26
0
Order By: Relevance
“…Cadmium stress-induced oxidative stress in pigeon pea was measured by the elevated contents of hydrogen peroxide, thiobarbituric acid reactive substances, and electrolyte leakage (Figure 2). Our findings are consistent with previous studies, where similar oxidative damage under cadmium exposure in other plant species has been reported [14][15][16].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Cadmium stress-induced oxidative stress in pigeon pea was measured by the elevated contents of hydrogen peroxide, thiobarbituric acid reactive substances, and electrolyte leakage (Figure 2). Our findings are consistent with previous studies, where similar oxidative damage under cadmium exposure in other plant species has been reported [14][15][16].…”
Section: Discussionsupporting
confidence: 94%
“…These growth-inhibiting effects of Cd on pigeon pea may be attributed to the significant decrease in photosynthetic activities, nutrient deficiency, and excessive ROS production (Tables 1 and 2; Figure 1). Previous studies have reported similar reduced growth attributes in other plant species due to cadmium stress [14,15,52,53]. Photosynthesis is plants' life-sustaining process and is often sensitive to metal stresses.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…PGPR release essential substances and increase nutrients availability which plays an important role in the synthesis of photosynthetic pigments which were required for the process of photosynthesis [ 44 ]. Zafar-ul-Hye et al [ 45 ] research show that Stemtrophomonas maltaphilia and Agrobacterium fabrum inoculation increased chlorophyll a chlorophyll b and total chlorophyll content in the bitter gourd in Cd contaminated soil. Plants facing heavy metal stress have reduced water uptake which decreases the photosynthetic capacity of plants and results in a reduced growth rate [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results were in agreement with that previously reported [ 35 ]. Previous reports have revealed that the environmental stresses considerably induce oxidative stress as well as the levels of electrolyte leakage (EL) and malondialdehyde (MDA) in different plant species, causing damages in plant tissues [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Similarly, in the current study, spinach plants also exhibited higher levels of EL and MDA in the absence of peptone treatment.…”
Section: Discussionmentioning
confidence: 99%